"Moving from uncertainty toward acceptance": a grounded theory study on exploring Iranian women's experiences of encountering menopause. (2nd April 2020) - Bahri, Narjes; Latifnejad Roudsari, Robab
Abstract: Purpose: Menopause as a universal phenomenon is influenced by social norms so that women's experiences during menopausal transition are related to the social values and cultural symbols. This qualitative study was conducted to discover the Iranian women's experiences of encountering menopause. Materials and Methods: In this grounded theory study 27 women living in Mashhad and Gonabad, North East of Iran, from May 2013 to July, 2016 were selected using purposive and theoretical sampling. Semi structured in-depth interviews were conducted for data collection until data saturation was achieved. Data was analyzed using Strauss and Corbin's (1998) recommended method through open, axial and selective coding. MAXQDA 2007 software was used for organizing data and managing the process of analysis. Results: The analysis revealed the core category of "moving from uncertainty toward acceptance". The interrelated categories subsumed under the core category included challenging aging, observing the symptoms of menopause, responding to the menopausal symptoms, understanding the need for preparation, and assessing the right time to prepare. Conclusion: Moving from uncertainty toward acceptance was identified as the core concept in the Iranian women's experiences of encountering menopause. Modifying the beliefs of people about menopause and aging as well as increasing their knowledge and information about menopause can help women to experience the menopausal transition with more ease.